Karakteristik Biopelet Dari Limbah Kulit Kelapa Muda Dan Batok Kelapa Menggunakan Perekat Getah Pinus Sebagai Bahan Bakar Alternatif - Aulia, Sekar; Ginting, Zainuddin; Muthawali, Dede Ibrahim; Ishak, Ishak; Muhammad, Muhammad; Kurniawan, Eddi; Kusuma, Budhi Santri (CV. IRA PUBLISHING, 2024)
Biopellets are an energy source derived from biomass that can serve as a substitute for fossil fuels. This study uses young coconut waste consisting of husks and shells and coconut shells as the main raw materials. This research aims to analyze the characteristics of bio pellets through proximate analysis, calorific value, density, and combustion rate tests. The bio-pellets are produced through a carbonization process using pine resin adhesive with varying raw material compositions of 100:0, 75:25, 50:50, 25:75, and 0:100, and adhesive concentrations of 10%, 20%, and 30%—previous research combined coconut shells with instant coffee grounds to create bio-pellets. The results of this study indicate that the best bio-pellets are made from a mixture of young coconut waste and coconut shells with a 25:75 ratio and 30% adhesive concentration. These bio-pellets have a moisture content of 7.0%, ash content of 0.8%, volatile matter of 14.76%, fixed carbon of 76.96%, combustion rate of 0.028 g/min, density of 1.410%, and a calorific value of 7468.51 cal/g, meeting the SNI 8021-2014 standards.